Pengaruh Pengetahuan, Kemudahan Penggunaan, dan Kredibilitas Terhadap Minat Penggunaan Quick Response Code Indonesian Standard (QRIS) (Studi Pada Generasi Z di Provinsi Bali): (Studi pada Generasi Z di Provinsi Bali) - Komang Erlita Agustina; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of knowledge, ease of use, and credibility on intention of use QRIS. This study is quantitative study with 400 respondents of generation Z in Bali Province who have used QRIS through the E-Wallet application as a method for payment transactions. The data obtained by distributing questionnaires using the Google Form media. The criteria for the selected samples were using the purposive sampling technique then calculated by the Slovin formula. The data of this study are the form of respondents’ answers as the primary data then processed using SPSS version 26. The data test tool used in this study was to test the quality of data consisting of validity and reliability test. After that, assumption testing consisting of normality test, multicollinearity test and heteroscedasticity test was used. The hypothesis testing used is the T test and coefficient of determination. The data were analyzed using multiple linear regression analysis. The results of this study indicate that knowledge, ease of use, and credibility partially have a positive and significant effect on intention of use QRIS.